The Effectiveness of Using The Duolingo Application to Enhance Students' English Vocabulary Mastery - Dinasti, Dinasti; Ilham, Ilham; Bafadal, Fauzi (Journal of English Language and Education, 2025)
This study aims to evaluate the effectiveness of the Duolingo application in enhancing students' English vocabulary mastery through a pre-experimental design. A total of 26 participants engaged in a two-week intervention using Duolingo to improve their vocabulary skills. The results of the pre-test and post-test assessments demonstrated a significant improvement in vocabulary mastery, with the mean score increasing from 63.42 to 85.08. The standard deviation decreased from 14.711 to 9.169, indicating greater consistency in student performance following the intervention. The paired samples correlation of 0.693 with a significance value of 0.000 indicated a strong positive relationship between the pre-test and post-test scores, supporting the effectiveness of the intervention. Further analysis using a paired samples t-test revealed a mean difference of -21.654 with a t-value of -10.363 (p 0.001), confirming that the intervention had a significant impact on vocabulary acquisition. The effect size calculation (Cohen's d = -2.032) indicated a large effect size, demonstrating the substantial impact of Duolingo on students’ vocabulary development. The study concludes that Duolingo can serve as an effective supplementary tool for vocabulary acquisition in English language learning. Future research is encouraged to explore the long-term effects of the application, its influence on other language skills, and its potential integration into formal educational contexts.